Coordinated control of acceleration slip regulation and active front steering for in-wheel motor driven electric vehicle based on dynamic slip ratio constraint - Zhigang Zhou; Wei Shen; Fang Xu; Ruili Yang (PLoS ONE, 2025)
In-wheel motor driven electric vehicles are prone to issues such as wheel spin, vehicle sideslip, fishtailing, and steering instability when traveling on compacted snow surfaces. While traditional optimal slip ratio tracking aims to maximize longitudinal force, it significantly compromises lateral force reserves. Moreover, most existing longitudinal-lateral coordination strategies fail to actively constrain the slip ratio, unable to prevent the deterioration of road adhesion conditions. To address these challenges, this study proposes a coordinated control strategy integrating acceleration slip regulation (ASR) and active front steering (AFS) under dynamic slip ratio constraints. To maximize the preservation of tire lateral force margin for enhanced anti-sideslip capability, a dynamic slip ratio constraint control method is proposed. With the objectives of dynamically minimizing wheel slip ratio and maintaining driving stability, the non-dominated sorting genetic algorithm-II (NSGA-II) is employed to optimally distribute the total driving torque. Furthermore, to counteract undesired yaw moments caused by uneven road friction coefficients or torque distribution, an active front steering (AFS) compensation control strategy based on sliding mode control (SMC) is designed to track the ideal yaw rate and sideslip angle, thereby achieving efficient coordination between acceleration slip regulation and yaw stability control. Co-simulations under various conditions are conducted using the Matlab/Simulink-CarSim platform. The results demonstrate that the proposed strategy effectively suppresses wheel spin, reduces lateral path tracking errors, and improves both longitudinal and lateral stability of the vehicle. This study provides an effective solution for enhancing the active safety control of in-wheel motor driven electric vehicles operating in icy and snowy environments.